Enteral feeding reduces metabolic activity of the intestinal microbiome in Crohn’s disease: an observational study - Walton, Christopher; Montoya, M. P. B.; Fowler, Dawn P.; Turner, Claire; Jia, W.; Whitehead, Rebekah N.; Griffiths, Lesley; Waring, Rosemary H.; Ramsden, David B.; Cole, Jeffrey A.; Cauchi, Michael; Bessant, Conrad M.; et al. (Nature Publishing Group, 2016)
BACKGROUND/OBJECTIVES: Enteral feeding will induce remission in as many as 80–90% of compliant patients with active Crohn’s disease (CD), but its method of action remains uncertain. This study was designed to examine its effects on the colonic microbiome. METHODS/SUBJECTS: Healthy volunteers and patients with CD followed a regimen confined to enteral feeds alone for 1 or 2 weeks, respectively. Chemicals excreted on breath or in faeces were characterised at the start and at the end of the feeding period by gas chromatography/mass spectrometry. RESULTS: One week of feeding in healthy volunteers caused significant changes in stool colour and deterioration in breath odour, together with increased excretion of phenol and indoles on the breath. Feeding for 2 weeks in patients with CD produced significant improvements in symptoms and a decrease in the concentration of C-reactive protein. The faecal concentrations of microbial products, including short-chain fatty acids (SCFAs), and potentially toxic substances, including 1-propanol, 1-butanol and the methyl and ethyl esters of SCFAs, showed significant falls. CONCLUSIONS: A significant change occurs in the production of microbial metabolites after enteral feeding in both healthy volunteers and patients with CD. Many of those detected in CD are toxic and may feasibly lead to the immunological attack on the gut microbiota, which is characteristic of inflammatory bowel disease. The reduction in the production of such metabolites after enteral feeding may be the reason for its effectiveness in CD.